2023
DOI: 10.18388/abp.2020_6539
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA-AnnexinA7 accelerates cisplatin resistance in non-small cell lung cancer via modulating microRNA-545-3p to mediate Cyclin D1

Abstract: Objective: To explore the mechanism of circular RNA (circRNA)-AnnexinA7 (ANXA7) in non-small cell lung cancer (NSCLC) cisplatin (DDP) resistance through microRNA (miR)-545-3p to target Cyclin D1 (CCND1). Methods: DDP-resistant and non-resistant NSCLC tissues and normal tissues were collected. DDP-resistant cells (A549/DDP and H460/DDP) were constructed. circ-ANXA7, miR-545-3p, CCND1, P-Glycoprotein, and glutathione S-transferase-π in tissues and cells were measured. Analysis of circ-ANXA7 ring structure was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Low levels of circRABL2B in plasma exosomes could distinguish early stage lung-cancer patients, and it was revealed that circRABL2B counteracts lung cancer progression via MUC5AC (Mucin 5AC, Oligomeric Mucus/Gel-Forming)/integrin β4/pSrc/p53 axis, making the circRABL2B potential therapeutic target ( Lu et al, 2023 ). An acceleration to cisplatin resistance in NSCLC patients by circ-ANXA7 was also recently reported ( Yao et al, 2023 ). A mechanism behind this was concluded to be the regulation of CCND1 (Cyclin D1) by circ-ANXA7 via miR-545-3p sponging.…”
Section: Role Of Circrnas In Lung Cancermentioning
confidence: 55%
“…Low levels of circRABL2B in plasma exosomes could distinguish early stage lung-cancer patients, and it was revealed that circRABL2B counteracts lung cancer progression via MUC5AC (Mucin 5AC, Oligomeric Mucus/Gel-Forming)/integrin β4/pSrc/p53 axis, making the circRABL2B potential therapeutic target ( Lu et al, 2023 ). An acceleration to cisplatin resistance in NSCLC patients by circ-ANXA7 was also recently reported ( Yao et al, 2023 ). A mechanism behind this was concluded to be the regulation of CCND1 (Cyclin D1) by circ-ANXA7 via miR-545-3p sponging.…”
Section: Role Of Circrnas In Lung Cancermentioning
confidence: 55%